2017
DOI: 10.3892/mmr.2017.6452
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorooctanoic acid induces oxidative damage and mitochondrial dysfunction in pancreatic β-cells

Abstract: Several environmental contaminants have been linked to the development of diabetes and increased diabetes‑associated mortality. Perfluorooctanoic acid (PFOA) is a widely used perfluoroalkane found in surfactants and lubricants, and in processing aids used in the production of polymers. Furthermore, PFOA has been detected in humans, wildlife and the environment. The present study investigated the toxic effects of PFOA on rat pancreatic β‑cell‑derived RIN‑m5F cells. Cell viability, apoptosis, reactive oxygen and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 63 publications
6
38
1
Order By: Relevance
“…While no remarkable changes were observed in earlier stage hearts, a significant increase in the ROS level was observed in ED19 chicken embryo hearts exposed to PFOA, suggesting the role of ROS in PFOA-induced developmental cardiotoxicity. This result is consistent with previous studies with PFOA [22,31]. Meanwhile, co-treatment with l -carnitine significantly decreased the ROS level in ED19 hearts, suggesting the anti-oxidant effects of l -carnitine, which may help to explain the protective effects exerted by l -carnitine.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…While no remarkable changes were observed in earlier stage hearts, a significant increase in the ROS level was observed in ED19 chicken embryo hearts exposed to PFOA, suggesting the role of ROS in PFOA-induced developmental cardiotoxicity. This result is consistent with previous studies with PFOA [22,31]. Meanwhile, co-treatment with l -carnitine significantly decreased the ROS level in ED19 hearts, suggesting the anti-oxidant effects of l -carnitine, which may help to explain the protective effects exerted by l -carnitine.…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that PFOA could induce ROS in various cell types and organisms [22,31], which might contribute to its toxicity. l -carnitine has been reported to possess anti-oxidant effects in multiple studies [20,32]; however, it may also promote ROS generation since it facilitates β-oxidation [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that PFOA is able to generate oxidative stress in various cell types and organisms . In our study, it was found that ROS levels increased significantly and in a concentration‐dependent manner in PFOA‐exposed ovaries ex vivo.…”
Section: Discussionsupporting
confidence: 90%
“…In mouse testis, the lowest dose tested of 2.5 mg/kg/day PFOA increased MDA and hydrogen peroxide levels, decreased the expression of the oxidant-sensitive transcription factor, Nrf2, and inhibited the activities of antioxidant enzymes (superoxide dismutase and catalase) [91]. PFOA also induces oxidative stress in a dose-dependent manner from 0.5 to 5 mg/kg/day in the mouse liver and pancreas [25], and a variety of tissues including rat pancreatic β-cells [92], mouse testes and epididymis [93], and mouse ovary [94]. Similarly, in vivo and in vitro studies have demonstrated that PFOS exposure results in oxidative stress, evidenced by the production of ROS, changes in antioxidant enzymes, elevation of lipid peroxidation products and changes in Nrf2 [32,[95][96][97].…”
Section: Induces Oxidative Stressmentioning
confidence: 95%